2012
DOI: 10.1053/j.ajkd.2011.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Discussions of the Kidney Disease Trajectory by Elderly Patients and Nephrologists: A Qualitative Study

Abstract: Background Elderly patients with advanced kidney disease experience considerable disability, morbidity, and mortality. Little is known about the impact of physician-patient interactions on patient preparation for the illness trajectory. We sought to describe how nephrologists and older patients discuss and understand the prognosis and course of kidney disease leading to renal replacement therapy. Methods We conducted focus groups and interviews with 11 nephrologists and 29 patients older than 65 years with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
200
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(210 citation statements)
references
References 41 publications
7
200
0
3
Order By: Relevance
“…One study found that less than 10% of CKD patients had discussed EOL care with health professionals, suggesting that more patients need to be given this opportunity 46 . A qualitative study found that ESKD patients tended to wait for health professionals to raise ACP rather than raise it themselves 48 , while another found that nephrologists discussed EOL issues based on prognosis but struggled to identify a suitable juncture 103 . Without appropriately sensitive communication about prognosis, patients on dialysis may dramatically over-estimate their life expectancy 104 .…”
Section: Discussionmentioning
confidence: 99%
“…One study found that less than 10% of CKD patients had discussed EOL care with health professionals, suggesting that more patients need to be given this opportunity 46 . A qualitative study found that ESKD patients tended to wait for health professionals to raise ACP rather than raise it themselves 48 , while another found that nephrologists discussed EOL issues based on prognosis but struggled to identify a suitable juncture 103 . Without appropriately sensitive communication about prognosis, patients on dialysis may dramatically over-estimate their life expectancy 104 .…”
Section: Discussionmentioning
confidence: 99%
“…Nephrologists may struggle to have these conversations (11), partly due to the relative lack of data concerning the likely trajectory of patients when dialysis is not utilized.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with kidney disease report being open to engaging in ACP but expect health care providers to initiate these conversations (13)(14)(15)(16)(17). Barriers to ACP among renal providers include inadequate knowledge and training in communication, belief that ACP may be distressing for patients, concerns that ACP is too time consuming, difficulty estimating prognosis, and uncertainty about their role in ACP (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%